Close, but not too close: a mesoscopic description of (a)symmetry and membrane shaping mechanisms. Issue 1 (31st March 2023) - Ruhoff, Victoria Thusgaard; Bendix, Poul Martin; Pezeshkian, Weria
Abstract : Biomembranes are fundamental to our understanding of the cell, the basic building block of all life. An intriguing aspect of membranes is their ability to assume a variety of shapes, which is crucial for cell function. Here, we review various membrane shaping mechanisms with special focus on the current understanding of how local curvature and local rigidity induced by membrane proteins leads to emerging forces and consequently large-scale membrane deformations. We also argue that describing the interaction of rigid proteins with membranes purely in terms of local membrane curvature is incomplete and that changes in the membrane rigidity moduli must also be considered.